Tinjauan Filsafat Hukum Islam dalam Pembagian Ahli Waris Pengganti - Afrizal Afrizal; Fauzan Fauzan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research examines the main question regarding the validity of substitute heirs from the perspective of Islamic legal philosophy, which has sparked debates among scholars concerning the application of justice and welfare principles in inheritance. The background of this issue stems from the absence of explicit provisions regarding substitute heirs in the Qur'an and hadith, while this phenomenon frequently occurs in modern inheritance practices. The novelty of this research lies in the legal-philosophical approach that links the concepts of justice, welfare, and continuity in inheritance distribution, exploring the views of both classical and contemporary scholars. This study uses a literature review method with a normative and comparative approach, analyzing Sharia principles and interpretations by Islamic jurists regarding substitute heirs. The findings reveal that while the concept of substitute heirs is not explicitly mentioned in the Qur'an, some scholars allow its practice based on principles of justice, welfare, and societal needs. This reflects the flexibility of Islamic law in addressing social dynamics without compromising core Sharia principles. The conclusion emphasizes the importance of considering social context and welfare in the application of Islamic inheritance law, while adhering to the justice principles taught by Sharia.